2023
DOI: 10.1002/smll.202302999
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Microdomain Factor Controls Interaction of Organic Halides with the Palladium Phase and Influences Catalytic Activity in the Mizoroki‐Heck Reaction

Abstract: In this work, using a combination of scanning and transmission electron microscopy (SEM and TEM), the transformations of palladium‐containing species in imidazolium ionic liquids in reaction mixtures of the Mizoroki‐Heck reaction and in related organic media are studied to understand a challenging question of the relative reactivity of organic halides as key substrates in modern catalytic technologies. The microscopy technique detects the formation of a stable nanosized palladium phase under the action of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…However, running the reaction using sodium iodide (NaI) and tetrabutylammonium iodide (TBAI) as an additive gave the expected aniline 3 in 22 % and 50 % yield respectively (entries 14 and 15). [22] Following the optimization studies, UV/Vis absorption studies were carried out to gain insight into the lightabsorbing nature of the divalent palladium. The solution of Pd(OAc) 2 in DMSO shows a broad absorption around 350-450 nm which are expected to be productive triplet transitions (Supporting Information Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, running the reaction using sodium iodide (NaI) and tetrabutylammonium iodide (TBAI) as an additive gave the expected aniline 3 in 22 % and 50 % yield respectively (entries 14 and 15). [22] Following the optimization studies, UV/Vis absorption studies were carried out to gain insight into the lightabsorbing nature of the divalent palladium. The solution of Pd(OAc) 2 in DMSO shows a broad absorption around 350-450 nm which are expected to be productive triplet transitions (Supporting Information Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…[15g] Aryl boronate that can undergo Suzuki coupling with aryl halides under the Pd-catalyzed conditions was also tolerated (19, 41 %) with deiodination and homocoupling side products. Subsequently, substituents at meta-and ortho-position of aryl iodide were varied (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Both the electron-rich (20-22) and -deficient (23)(24)(25) substrates at the meta-position gave the free aniline in good to moderate yields (66-85 %).…”
Section: Resultsmentioning
confidence: 99%
“…As expected, under the standard conditions, bromobenzene provided lower yield, since its oxidative addition to the electrophilic Pd II is difficult at room temperature (entry 13). However, running the reaction using sodium iodide (NaI) and tetrabutylammonium iodide (TBAI) as an additive gave the expected aniline 3 in 22 % and 50 % yield respectively (entries 14 and 15) [22] …”
Section: Resultsmentioning
confidence: 99%
“…The rational design of chemical transformations in such complex reaction environments is unthinkable without a clear understanding of the nature of the key phenomena occurring not only at the nanoscale but also at higher levels of matter organization. Moreover, recent experimental observations , have revealed that the microscale attributes of a chemical system can markedly modulate the reaction dynamics.…”
Section: Introductionmentioning
confidence: 99%